EFFECTS OF THE EYE TRACKER TRAINING PROGRAM FOR STUDENTS WITH NEUROMUSCULAR DISEASE - Fanti, Juliana Roberta [UNESP]; Braccialli, Ligia Maria Presumido [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
That Article presents part of an research of master's degree that was elaborated, applicated and analyzed an training program of use of eye tracking as dispositive access to computer to students with neuromuscular diseases, checking the effects about the motor performance. The research characterizes as experimental with outline as subject unique as type A-B-A. The resource variety where accurate, reaction time,moviment time and error, measured by the softwares Discrete Aiming Task 2.0,Tracking Task 2.0 and Single Switch Performance Test 1.0. The results demonstrate positive changes on motor perfomance, except on error frequency, that raised proportionally to the percentage of moving time, showing an positive relation between the variants, on the demanding of the task. It oncludes that the training program raised up the motor performance of the student that used eye tracking, giving independency to the source on school ambient.
Keywords: Special education; Supportive tecnlogy; Neuromuscular diseases; Eye tracking; Motor learning